(untitled) (Eurasian Research Bulletin, 2023)
Biosurfactants are surface active amphiphilic compounds of biological origin and produced by many different microorganisms. The microorganisms including bacteria, fungi and algae are the most efficient organisms at producing biosurfactants. The biosurfactants offer many advantages compared to the synthetic surfactants: they are environmentally friendly, have useful properties including bioavailability, biodegradability, activity under extreme conditions, low toxicity and structural diversity. The purpose of this work was obtaining new biosurfactants from microorganisms, investigating the colloid-chemical properties of new biosurfactants, the efficiency of biosurfactants water solutions on wettability of different surfaces and establishing correlations between colloid-chemical properties of new surfactants. The modern methods for determining the colloid-chemical and solution properties of biosurfactants were used in the work. The contact angles of biosurfactant water solutions on different hydrophilic and hydrophobic surfaces were investigated. It has been established that the contact angles of biosurfactant water solutions on the hydrophilic surfaces (aluminum, copper, steel, glass) significantly depends on the composition and structure of biosurfactant molecules. It has been shown, that the compositions with low biosurfactant concentrations have higher contact angles and the hydrophobization of aluminum, copper, steel and glass surfaces takes place. At high biosurfactant concentrations, the contact angles sharply decreased due to the fact that during adsorption, the biosurfactant